2014
DOI: 10.3390/soc4040549
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Cyberbullying among College Students: Hacking, Dirty Laundry, and Mocking

Abstract: Bullying behaviors occur across the lifespan and have increasingly migrated to online platforms where they are known as cyberbullying. The purpose of this study was to explore the phenomenon of cyberbullying among college students. Participants were recruited for focus groups through purposeful sampling, including recruitment from groups traditionally at risk for bullying. Focus groups discussed views and perceptions of cyberbullying on campuses. Groups were led by a trained facilitator and were audio recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Lund and Ross (2016) concluded that certain students in college may face biases and aggression online due to their minority status. Among college students, cyberbullying often involved romantic relationships, including break-ups and revenge (Crosslin & Goldman, 2014; Kota, Schoohs, Benson, & Moreno, 2014; Rafferty & Vander Ven, 2014). These studies noted that anonymity plays a large role in cyberbullying on college campuses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lund and Ross (2016) concluded that certain students in college may face biases and aggression online due to their minority status. Among college students, cyberbullying often involved romantic relationships, including break-ups and revenge (Crosslin & Goldman, 2014; Kota, Schoohs, Benson, & Moreno, 2014; Rafferty & Vander Ven, 2014). These studies noted that anonymity plays a large role in cyberbullying on college campuses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, aggressive behavior is typical of bullying but cyberbullying actions can be passive although still hurtful. Like bullying, cyberbullying involves behaviors which are intended to hurt or publicly shame another individual, but some can be unintended, like a joke that goes too far, or involve what might be viewed as excessive/annoying behavior (Kota, Schoohs, Benson, & Moreno, 2014;Slonje & Smith, 2008). Also, without the constraints of time and space, cyberbullying actions can occur in front of larger virtual audiences with the support of a range of media such as photos or videos, and, by going viral, can be unintentionally repeated through shared information.…”
Section: Introductionmentioning
confidence: 99%
“…Within this definition, 4 different types of bullying behavior are commonly identified: physical, verbal, relational, and damage to property [6]. Observational studies have shown that the different forms of bullying of youths may overlap [8,9]. Within the CDC definition, cyberbullying is considered bullying by digital electronic means.…”
Section: Introductionmentioning
confidence: 99%